Evaluating communication in healthcare: Systematic review and analysis of suitable communication scales. (December 2013) - Ang, Wee Choen; Swain, Nicola; Gale, Christopher
Abstract : Communication influences health outcomes such as health status, adherence, and satisfaction. It is also highly modifiable, so it should be a target of intervention studies. However, measurement of communication can be difficult, as many scales exist and there is no clear guidance on which to use in a healthcare setting. We performed a systematic review conducted in four article databases (PubMed, Medline, Embase, and PsychINFO). The initial search yielded nine satisfactory scales. An in-depth analysis based on their content, readability, and psychometric properties determined two communication scales to be most suitable: the Communication Adaptability Scale and the Interpersonal Communication Competence Scale. This finding may make selection of an instrument to measure communication in intervention studies in healthcare more straighforward.